A Systematic Review of Research on Guided Access Cavity Preparation Endodontic Treatment: Dentin Preservation Perspectives - Muryani A; Aripin D; Dharsono HDA; Rajion ZA; Wicaksono S (Clinical, Cosmetic and Investigational Dentistry)
Anna Muryani,1,2 Dudi Aripin,2 Hendra Dian Adhita Dharsono,2 Zainul Ahmad Rajion,3 Satrio Wicaksono4 1Doctoral Programme Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 2Conservative Dentistry Department Faculty of Dentistry, Universitas Padjadjaran, Bandung, West Java, Indonesia; 3Department Oral Maxillofacial Surgery and Oral Diagnosis Kulliyyah of Dentistry International Islamic University Malaysia, Kuantan, Malaysia; 4Faculty of Mechanical and Aerospace Engineering, Institut Teknologi Bandung, Bandung, West Java, IndonesiaCorrespondence: Anna Muryani, Gedung Pamitran Unpad, lantai 4 Wing Utara Jl. Prof. Eyckman No. 38 Bandung, Faculty of Medicine, Universitas Padjadjaran, West Java, Indonesia, 40161, Tel +62 896 1997 2132, Email anna.muryani@unpad.ac.idPurpose: Guided access cavity preparation (GACP) is an endodontic procedure utilizing stents, guide sleeves, or dynamic guides to facilitate the proper formation of access cavities. This paper aims to evaluate the significance of research on guided access cavity preparation in endodontic treatment concerning dentin preservation. In the context of dentin preservation, this paper provides a thorough scoping review of a variety of methodologies for evaluating the accuracy of guided access cavity preparation.Materials and Methods: Article searches were conducted using Tthe keywords ”Guide Access Cavity Preparation” AND “Static Guide OR 3D Printing Template” AND ”Dynamic Guide through digital databases including PubMed, Scopus, Cochrane Library, Science Direct, and Google Scholar. Research articles published in English within the past five years (2019-2024) and in accordance with the PCC (Population, Concept, and Context) framework were also included in the study. Articles from the meta-analysis or systematic review study type, those that were not accessible in full text or in a paid format, and those that did not assess the use of guided endodontics in endodontic surgery were excluded. This scoping review adheres to the Preferred Reporting Items for Systematic Reviews without Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) criteria.Results: A total of 12 articles were reviewed, encompassing various locations, designs, type, and samples, which demonstrated the use of guided access cavity preparation has significant clinical applications and can provide accurate results in endodontic therapy.Conclusion: Article searches were conducted using the keywords “Guide Access Cavity Preparation” AND ‘Static Guide OR 3D Printing Template’ AND” Dynamic Guide through digital databases including PubMed, Scopus, Cochrane Library, Science Direct, and Google Scholar. Research articles published in English within the past five years (2019– 2024) and in accordance with the PCC (Population, Concept, and Context) framework were also included in the study. Articles from the meta-analysis or systematic review study type, those that were not accessible in full text or in a paid format, and those that did not assess the use of guided endodontics in endodontic surgery were excluded. This scoping review adheres to the Preferred Reporting Items for Systematic Reviews without Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) criteria. Studies show that advanced technologies in guided access cavity preparation endodontic treatment can improve dentin preservation, improve accuracy and predictability, particularly for root canal anomalies and difficult teeth, but clinicians must consider limitations and clinical applications. Clinicians must evaluate the limitations and clinical applications of guided endodontic access prior to its implementation.Keywords: guided endodontic access, GEA, guided access cavity preparation, GACP, static guided endodontic access, SGEA, dynamic guide endodontic access, DGEA, preservation dentin